Importance of prognostic nutritional index in on-pump coronary artery bypass graft surgery - Gucu, Arif (The European Research Journal, 2021)
Objectives: A simple and appropriate risk index is still required to show the patient's nutritional status undergoing coronary artery bypass graft (CABG) surgery. This study aimed to evaluate the Prognostic Nutritional Index (PNI) value as a predictor of in-hospital mortality in patients undergoing CABG surgery. Methods: In this study, we scanned the medical data of 742 patients’ who underwent on-pump CABG surgery retrospectively. Patients' were divided into two groups based on the PNI cut-off value (high-risk group, PNI < 45.85, n = 230; low-risk group, PNI ≥ 45.85, n = 512). Results: To analyze the factors affecting in-hospital mortality in the postoperative period, univariate and multivariate logistic regression analysis was performed. In univariate analysis, advanced age (Odds ratio (OR): 1.219, 95% confidence interval (CI): 1.194-2.669, p < 0.001), left ventricular ejection fraction (LVEF) (OR: 3.471, 95% CI: 2.854-6.927, p < 0.001), total perfusion time (OR: 0.876, 95% CI: 0.690-0.954, p = 0.012), intra-aortic balloon pump (IABP) use (OR: 2.148, 95% CI: 1.394-2.889, p = 0.002), preoperative high creatinine (OR: 1.229, 95% CI: 1.066-2.118, p = 0.019), low lymphocyte count (OR: 0.879, 95% CI: 0.789-0.945, p = 0.017), low albumin (OR: 1.682, 95% CI: 1.433-2.765, p = 0.003), high C-reactive protein (CRP) (OR: 1.0.790, 95% CI: 0.678-0.927, p = 0.042) and low PNI (OR: 1.290, 95% CI: 1.119-1.654, p < 0.001) were correlated with the postoperative mortality. In multivariate logistic regression analysis, advanced age (OR: 1.145, 95% CI: 1.110-1.938, p = 0.017), LVEF (OR: 2.916, 95% CI: 1.768-4.928, p < 0.001), IABP use (OR: 1.880, 95% CI: 1.350-2.554, p = 0.032) and PNI (OR: 0.932, 95% CI: 0.889-0.978, p = 0.004) were independent predictors of mortality. Conclusions: In on-pump CABG surgery, postoperative mortality is associated with low preoperative PNI, and can be a useful and suitable parameter for preoperative risk evaluation.